Ecological risk assessment of microplastics contamination in water, sediment and native fish species of the Brahmaputra River, India - Dhruba Jyoti Sarkar; Siddharth Kumar Jatav; Rakesh Kumar; Soma Das Sarkar; Simanku Borah; Ajoy Saha; Santhana Kumar Vanniaraj; Tuhin Sikdar; Basanta Kumar Das (Journal of Contaminant Hydrology, 2026)

Resilience of fish assemblages to a short-term perturbation: a case study of the Siang River in the Eastern Himalayas - Simanku Borah; Pranab Gogoi; Kavita Kumari; Shyamal Chandra Sukla Das; Amulya Kakati; Bipul Chandra Ray; Birendra Kumar Bhattacharjya; Sanjoy Kumar Das; Srikanta Samanta; Vettath Raghavan Suresh; Sullip Kumar Majhi; Basanta Kumar Das (Environmental Monitoring and Assessment, 2026)

Advanced Machine Learning and Statistical Modelling for the Assessment of Water Quality and Trophic Dynamics in the Upper and Middle Ganga River Basin - Jeetendra Kumar; Basanta Kumar Das; Asha T. Langde; Absar Alam; Ajoy Saha; Shashi Bhusan; Vikas Kumar; Rayees Ahmad Bhatt; Simanku Borah; Nitesh Kumar Sharma (Water, Air, & Soil Pollution, 2026)

A Study on the Risk-Spreading Reproductive Strategy in Landlocked Populations of Anadromous Tropical Shad, Tenualosa Ilisha (Hamilton, 1822), from Ukai Reservoir, in Comparison to their Anadromous Counterparts of Narmada Estuary, India - Gopinatha Pillai Vaisakh; Simanku Borah; Geetanjali Deshmukhe; Ashok Kumar Jaiswar; Amiya Kumar Sahoo; Basanta Kumar Das (Thalassas: An International Journal of Marine Sciences, 2025)

Integrated biomarker response in common carp fingerlings exposed to neonicotinoid insecticide imidacloprid - Hemanta Pokhrel; Raktim Sarmah; Darshana Sharma; Lucy Ingtipi; Naznin Ahmed; Sarada Kanta Bhagabati; Rajdeep Dutta; Arnab Narayan Patowary; Simanku Borah; Utpal Kumar Das; Debojit Dekari; Biswajyoti Bordoloi (Ecotoxicology, 2025)

Phytoplankton functional groups regulated by hydrological parameters in cascading reservoirs of the subtropical Ganga River, India - Jeetendra Kumar; Basanta Kumar Das; Asha Taterao Landge; Absar Alam; Ajoy Saha; Shashi Bhusan; Sandeep Kumar Mishra; Simanku Borah (Aquatic Ecology, 2025)

Preliminary Insights into the Environmental Drivers of Coscinodiscus Bloom in a Tropical Estuary - Muzammal Hoque; Sahina Akter; Sonam Angmo; Karankumar Ramteke; Sreekanth GB; Shashi Bhushan; Bejawada Chanikya Naidu; Simanku Borah; Binaya Bhusan Nayak; Asha T. Landge (Thalassas: An International Journal of Marine Sciences, 2025)

Improving approaches towards climate-smart wetland fisheries with a focus on small indigenous fishes - Sanjeet Debnath; Gunjan Karnatak; Mishal Puthiyottil; Lianthuamluaia Lianthuamluaia; Suman Kumari; Bandana Das Ghosh; Snigdhodeb Dutta; Simanku Borah; Uttam Kumar Sarkar; Basanta Kumar Das (Sustainable Water Resources Management, 2025)

Fish community structure in accordance with environmental signatures in a tropical river ecosystem in the Eastern Himalayan ecoregion - Shamyung O. Ongh; Asha Taterao Landge; Karankumar Ramteke; Simanku Borah; Jyotish Barman; Sahina Akter; Anil Kumar Yadav; Pritam Das; Sullip Kumar Majhi; Nabanita Chakraborty; Basanta Kumar Das (Aquatic Sciences, 2025)

Chemometric Assessment of Anthropogenically Impacted Ancient Artificial Wetland, Bhojtal, India, for its Drinking Water Suitability and Hydrogeochemical Classification - Rakesh Kumar; Md Basit Raza; Sangeeta Lenka; Simanku Borah; Anil Kumar Yadav; Dinesh Kumar Yadav; Roomesh K. Jena; Dhruba Jyoti Sarkar; Dharmendra Singh; Narendra Kumar Lenka; Rameshwar S. Kanwar; Sullip Kumar Majhi; et al. (Water, Air, & Soil Pollution, 2025)

Phytoplankton-environment dynamics in a tropical estuary of the northeastern Arabian Sea: a Generalized Additive Model (GAM) approach - Sahina Akter; Abhilash Wodeyar K; Suman Nama; Simanku Borah; Sonam Angmo; Geetanjali Deshmukhe; Binaya Bhusan Nayak; Karankumar Ramteke (Environmental Monitoring and Assessment, 2025)

Understanding and addressing microplastic pollution: Impacts, mitigation, and future perspectives - Rajesh Debnath; Gora Shiva Prasad; Adnan Amin; Monisa M. Malik; Ishtiyaq Ahmad; Adnan Abubakr; Simanku Borah; Mohd Ashraf Rather; Federica Impellitteri; Ifra Tabassum; Giuseppe Piccione; Caterina Faggio (Journal of Contaminant Hydrology, 2024)

Ecosystem-based fishery enhancement through pen culture of Indian major carp Labeo catla in a tropical floodplain wetland of North Eastern Region, India, during COVID pandemic - Simanku Borah; Basanta Kumar Das; Birendra Kumar Bhattacharjya; Anil Kumar Yadav; Pronob Das; Shyamal Chandra Sukla Das; Dharmendra Kumar Meena; Pranaya Kumar Parida; Mishal Puthiyottil; Raju Baitha; Jeetendra Kumar; Bhrigumani Dewan; et al. (Environmental Science and Pollution Research, 2024)

Understanding and approaches towards circular bio‐economy of wastewater reuse in fisheries and aquaculture in India: An overview - Shib Kinkar Das; Bithilekha Mondal; Uttam Kumar Sarkar; Basanta Kumar Das; Simanku Borah (Reviews in Aquaculture, 2023)
Circular bio‐economy of biogenic resources designates the plunging use of such resources, adopting a systemically formatted pathway towards sustainable economic development. Aquaculture has been perceived to play a pivotal role in supplying protein and mineral rich organic food to a growing human population. The exponential growth of aquaculture sector during the last four decades has established itself in a fundamental way to supply the global need of valuable animal protein. However, the on‐going production strategies may likely be proved unsustainable if the present level of exploitation and resource use continues. Emphasis only on augmenting productivity and yield with insufficient and/or inefficient pollution control measures, and water quality clean‐ups, direct discharge of effluents in the open ambient environment from aquaculture production systems have manifested in variable degrees of pollution particularly in the open water bodies; thereby causing significant impairment of these ecosystems. The paper discusses the various techniques of bioprocessing in re‐circulatory aquaculture system, aquaponics, biofloc technology, waste water aquaculture and circular enclosure culture for inland water bodies to recycle the waste generated from fisheries and aquaculture and converting the same to fish flesh, at the same time reducing the impact on environment. The study also highlights the potential attributes and benefits of circular bio‐economy, discusses recent advances and updates the current status of knowledge base for future research planning towards sustainability. Rationality perspectives of the system design with regards to simplicity, energy efficiency and budget in attaining circularity emerged as pertinent factors in bio‐circularity in resource use in aquaculture.

Influence of barrages on hydrological parameters and functional groups of phytoplankton of a subtropical river Ganga, India - Jeetendra Kumar; Absar Alam; Simanku Borah; Pranab Gogoi; Basanta Kumar Das (Environmental Science and Pollution Research, 2023)

Understanding the breeding phenology of anadromous fish Tenualosa ilisha (Hamilton, 1822) in relation to climatic variables in Brahmaputra River, India - Simanku Borah; Amiya Kumar Sahoo; Vaisakh Gopinathapillai; Dharmendra Kumar Meena; Ashok Kumar Jaiswar; Geetanjali Deshmukhe; Anil Kumar Yadav; Pranab Gogoi; Debasmita Mohanty; Karankumar Ramteke; Birendra Kumar Bhattacharjya; Basanta Kumar Das (Frontiers in Marine Science, 2023)
The Hilsa, Tenualosa ilisha , commands a very high value as food fish. The present study was carried out to understand the breeding phenology of T. ilisha in relation to climatic variables. Monthly fish samples were collected from two landing centres, namely, Uzanbazar (Guwahati) and Shri Ramghat, Dhubri, of River Brahmaputra during May 2018 to April 2019. The assessment of gonadosomatic index (GSI) of T. ilisha revealed higher GSI values during October to February, and showed temporal variations with respect to sex. In males, highest GSI value was observed in the month January followed by February, whereas in females, GSI value was found to be highest in November followed by October. GSI (pooled) value was negatively correlated with air temperature, indicating vulnerability of the species to climate change. The highest percentage of mature males was observed during October–February, and mature females during October–December. The length at first maturity was recorded to be 290 mm for female(s) and 259 mm for male(s). The absolute fecundity ranged from 103,164 to 583,456 ova for fishes in the size range of 229–403 mm, with an average of 250,532 ova per female. Relative fecundity was found to range from 306 to 1096 ova per gram body weight, with an average of 791 ova per gram body weight. The diameter of ova of the studied fishes ranged from 414.6 to 738.2 µm, with a mean value of 546.73 ± 7.18 µm. The percentage frequency distribution of mature ova shows a distinct single peak or mode. Sex ratio (male: female) was found to be 1:0.87, indicating dominance of males over females. The chi-square test on observed sex ratio against the hypothetical ratio of 1:1 did not reveal a significant difference ( p > 0.05). The findings of the present study can provide impetus toward successful management of this highly prized, transboundary, and migratory resource of River Brahmaputra, in the context of changing climate.

Impact of barrages on assemblage pattern of phytoplankton in tropical river Ganga, India - Jeetendra Kumar; Absar Alam; Dharm Nath Jha; Pranab Gogoi; Simanku Borah; Basanta Kumar Das (Environmental Monitoring and Assessment, 2022)

Assessing assemblage pattern, health status and environmental drivers of macrobenthic invertebrate community structure for sustainable management in a tropical tributary of River Ganga, India - Shyamal Chandra Sukla Das; Dharm Nath Jha; Absar Alam; Simanku Borah; Vijay Kumar; Kalpana Srivastava; Venkatesh Ramrao Thakur; Amiya Kumar Sahoo; Basanta Kumar Das (Sustainable Water Resources Management, 2022)

Integration of pen aquaculture into ecosystem-based enhancement of small-scale fisheries in a macrophyte dominated floodplain wetland of India - Gunjan Karnatak; Basanta Kumar Das; Uttam Kumar Sarkar; Simanku Borah; Aparna Roy; Pranay Parida; Lianthuamluaia Lianthuamluaia; Archan Kanti Das; Bijay Kumar Behera; Arun Pandit; Amiya Kumar Sahoo; Birendra Kumar Bhattacharjya; et al. (Environmental Science and Pollution Research, 2022)

Managing floodplain wetlands through culture-based fisheries (CBF) for livelihood security and sustainable development: a study from a biodiversity hotspot region of India - Simanku Borah; Uttam Kumar Sarkar; Pronob Das; Anil Kumar Yadav; Mishal Puthiyottil; Deisaulungbe Pame; Birendra Kumar Bhattacharjya; Basanta Kumar Das (Arabian Journal of Geosciences, 2022)

Status, Potential, Prospects, and Issues of Floodplain Wetland Fisheries in India: Synthesis and Review for Sustainable Management - Uttam Kumar Sarkar; P. Mishal; Simanku Borah; Gunjan Karnatak; Ganesh Chandra; Suman Kumari; D. K. Meena; Dipesh Debnath; Sona Yengkokpam; Pronob Das; Piyashi DebRoy; Anil K. Yadav; et al. (Reviews in Fisheries Science & Aquaculture, 2021)